Quantitative cellular uptake, localization and cytotoxicity of curcumin in normal and tumor cells - Kunwar, A.; Barik, A.; Mishra, B.; Rathinasamy, K.; Pandey, R.; Priyadarsini, K.I. (Biochimica et biophysica acta, 2008)
Using absorption and fluorescence spectroscopic methods, quantitative cellular uptake of curcumin, an antioxidant and anti-tumor agent from Curcuma longa, was calculated in two types of normal cells: spleen lymphocytes, and NIH3T3 and two tumor cell lines: EL4 and MCF7. Both the uptake and fluorescence intensity of curcumin were significantly higher in tumor cells compared to the normal cells. A linear dependency on the uptake was observed with treatment concentration of curcumin. Using laser confocal microscopy, intracellular localization of curcumin was monitored and the results indicated that curcumin is located both in the cell membrane and the nucleus. Sub-cellular fractionation of curcumin-loaded MCF7 cells supported the differential distribution of curcumin in membrane, cytoplasm and nuclear compartments of cell with maximum localization in the membrane. Cytotoxicity studies in different cell lines indicated that the toxicity of curcumin increased with increasing uptake.